Evaluating Teach One Reach One—An STI/HIV Risk-Reduction Intervention to Enhance Adult–Youth Communication About Sex and Reduce the Burden of HIV/STI. Issue 6 (November 2017) - Dave, Gaurav; Ritchwood, Tiarney; Young, Tiffany L.; Isler, Malika Roman; Black, Adina; Akers, Aletha Y.; Gizlice, Ziya; Blumenthal, Connie; Atley, Leslie; Wynn, Mysha; Stith, Doris; Cene, Crystal; et al.
Purpose: Parents and caregivers play an important role in sexual socialization of youth, often serving as the primary source of information about sex. For African American rural youth who experience disparate rates of HIV/sexually transmitted infection, improving caregiver–youth communication about sexual topics may help to reduce risky behaviors. This study assessed the impact of an intervention to improve sexual topic communication. Design: A Preintervention–postintervention, quasi-experimental, controlled, and community-based trial. Setting: Intervention was in 2 rural North Carolina counties with comparison group in 3 adjacent counties. Subjects: Participants (n = 249) were parents, caregivers, or parental figures for African American youth aged 10 to 14. Intervention: Twelve-session curriculum for participating dyads. Measures: Audio computer-assisted self-interview to assess changes at 9 months from baseline in communication about general and sensitive sex topics and overall communication about sex. Analysis: Multivariable models were used to examine the differences between the changes in mean of scores for intervention and comparison groups. Results: Statistically significant differences in changes in mean scores for communication about general sex topics ( P < .0001), communication about sensitive sex topics ( P < .0001), and overall communication about sex ( P < .0001) existed. Differences in change in mean scores remained significant after adjusting baseline scores and other variables in the multivariate models. Conclusions: In Teach One Reach One intervention, adult participants reported improved communication about sex, an important element to support risk reduction among youth in high-prevalence areas.